Pengaruh Thinking Style Tipe II terhadap Efikasi Diri Keputusan Karier yang Dimediasi oleh Planned Happenstance Skills pada Remaja - Rosliyanti Sofyan; Wahyu Indianti (Provitae: Jurnal Psikologi Pendidikan, 2019)
The aim of this study is to examine the impact of type II thinking style on career decision self-efficacy through planned happenstance skills through mediation of planned happenstance skills in adolescence. There was 720 students from three excellence schools who were participated in this quantitative study. The data were collected by using three scales: Career Decision Self-Efficacy Scale-Short Form, Thinking Style Inventory – Revised II, and Planned Happenstance Career Inventory, that have been adapted to Indonesian version by the researcher and previous researchers. The researchers were used macro PROCESS to analyzed the data. The result showed type II thinking style can affect career decision self-efficacy partially ( c = .3280, p = .0000; c’ = .1917, p = .0000). Based on the result of this study, we concluded when adolescents have good quality of planned happenstance skills, it can help adolescence who have type II thinking style have a good career decision self-efficacy.